The complete chloroplast genome sequence of Oxystophyllum changjiangense (Orchidaceae). Issue 9 (2nd September 2021) - Wang, Mengting; Yang, Jiapeng; Xue, Qingyun; Liu, Wei; Niu, Zhitao; Ding, Xiaoyu
Abstract: Oxystophyllum changjiangense has high economic value due to its wide applications in horticultural and medicinal fields. Here, the first chloroplast genome of O . changjiangense was sequenced and reported. The chloroplast genome displayed the typical quadripartite structure containing a pair of inverted repeats (IR), a long single-copy region (LSC), and a short single-copy region (SSC). Total 110 genes were found including 76 protein-coding genes, 30 tRNA genes, and four rRNA genes. Phylogeny analysis showed O . changjiangense has a close relationship with Phaius species.